Dilema Independensi dan Ketahanan Bisnis Media Lokal dalam Perspektif Konvergensi Media - Kusumo, Herlambang Jati; Agustia Leriani , Olla; Valiant Putra Alfa , Ditto; Zahra Saharani, Widya (Universitas Muhammadiyah Prof. DR. Hamka, 2026)
Mass media, as the fourth pillar of democracy, faces pressure from digital disruption, declining advertising revenue, and government budget efficiency policies. These conditions place local media in a dilemma between sustaining their business operations and maintaining editorial independence. This study aims to analyze how the media respond to these challenges through media convergence and digital transformation. This research employs a qualitative comparative approach focusing on Harian Jogja and Tribun Jogja. A comparative analysis was conducted to identify patterns of adaptation, business strategies, and practices of journalistic independence in both media outlets. The findings indicate that media convergence has become a key survival strategy amid changes in the media industry ecosystem. Both media outlets have developed digital platforms and social media, restructured newsroom operations, and encouraged journalists to work across multiple platforms. However, differences in adaptive orientation are evident. Harian Jogja emphasizes a balance between digital speed and content depth while developing business diversification grounded in the local context. In contrast, Tribun Jogja is more oriented toward optimizing digital networks, audiovisual content, and traffic-based strategies. Both media outlets strive to safeguard independence through the separation of advertising and news content, adherence to journalistic codes of ethics, and the strengthening of newsroom governance, despite increasing economic pressures. This study affirms that media convergence at the local level is not merely a technological adaptation, but a survival strategy aimed at balancing economic sustainability and journalistic ideals